AB0310 THE INCIDENCE OF EXTRA-ARTICULAR MANIFESTATIONS IN SOUTHERN CHINESE PATIENTS WITH INFLAMMATORY JOINT DISEASES. (June 2019) - Yan, Siyu; Cui, Yang; Zhang, Xiao
Abstract : Background: Inflammatory joint diseases (IJDs) are chronic arthritis, but frequently present with co-morbidities of other organs and systems, which is known as extra-articular manifestations (EAMs) 1 . It is still unclear which clinical characteristics or bio-markers can predict the development of EAMs 2 . Objectives: The aim of this study was to estimate the proportion of EAMs in southern Chinese patients with IJDs and to explore the risk factors. Methods: This was a retrospective cohort study of a total 1135 IJDs patients, including 788 rheumatoid arthritis (RA) patients, 307 ankylosing spondylitis (AS) patients and 40 psoriatic arthritis (PsA) patients. Demographic data, disease characteristics, laboratory blood tests, medical imaging, and the presence of EAMs were recorded. Results: We found 459 (40.44%) of them presented with EAMs: 30.84% had cardiovascular; 7.67% had pulmonary, 5.29% had osteoporosis/low bone mineral density, 2.29% had ocular, 0.79% had gastrointestinal and 0.26% had renal involvements. Multivariate logistic regression showed older age (OR: 1.05, P<0.001) and higher anti-cyclic citrullinated peptide antibody (anti-CCP) levels (OR: 1.003, P=0.011) were independent risks of EAMs in RA patients. In AS group, older age (OR: 1.07, P<0.001) and higher disease activity (OR: 2.06, P<0.001), were independent risks of EAMs. As in PsA group, longer disease duration (OR: 1.01, P=0.046) and higher disease activity (OR: 1.15, P=0.011) were independent risks. Conclusion: These results suggested the high prevalence of EAMs, and it is important to regularly screen on EAMs, as it influences treatment decision and impacts on patients' quality of life. References: [1] Agca R, Heslinga SC, van Halm VP, Nurmohamed MT. Atherosclerotic cardiovascular disease in patients with chronic inflammatory joint disorders. Heart2016;102:790-5. [2] Carmen Stolwijk AvT, José Dionisio Castillo-Ortiz AB. revalence of extra-articular manifestations in patients with ankylosing spondylitis: a systematic review and meta-analysis. Ann Rheum Dis2015;74:65–73. Disclosure of Interests: None declared